Analisis Risiko Ergonomi di Unit Rekam Medis Rumah Sakit Bhayangkara Bondowoso - Adelia Nuranisah Suyuti; Gandu Eko Julianto Suyoso; Rossalina Adi Wijayanti; Gamasiano Alfiansyah (Manajemen Pelayanan Kesehatan, 2024)
The management activities in medical records unit involve several occupational risks, one of which is ergonomic risk. It has been found that the space between shelves for staff movement is too narrow, and the condition of shelves and work chairs for staff is not ergonomic. This could increase risk of accidents and work-related illnesses. Objective of this study is to analyze ergonomic risks in medical records unit of Bhayangkara Bondowoso Hospital. This research is descriptive in nature and employs data collection techniques including interviews, observations, documentation, and measurements. The study utilizes HIRARC method (Hazard Identification, Risk Assessment, and Risk Control). Subjects of the study include four medical records staff members, head of medical records, and hospital's K3 committee. The study identified high ergonomic risks, such as non-ergonomic chairs and handling a large volume of retention files. Medium risks involved non- ergonomic shelves, prolonged computer use, working room, and narrow shelf spacing. Control measures included replacing facilities with ergonomic ones, conducting retention, destruction, and implementing EMR systems.